From innovation to exnovation : insights from post-growth food enterprises in Australia - Chakori, Sabrina; Grigg, Nicola J.; Biely, Katharina; Hinton, Jennifer B.; Plumecocq, Gaël; Richards, Russell; Robra, Ben (Ecological Economics, 2026)
This study explores systemic barriers and enablers of post-growth food enterprises in Australia. We analyse three different case studies that offer alternative models of entrepreneurial approaches for achieving sustainability outcomes as a higher priority than economic growth. We identified three post-growth food enterprises that operate at different stages of the food supply chain. We found that these enterprises work towards various, interconnected, sustainability goals by embedding diverse principles into their organisational structure and operations. Their not-for-profit structure enables them to avoid trade-offs between financial extractivism and socio-ecological well-being goals. Additionally, we explored the systemic barriers faced by these enterprises, recognising that they are embedded in an economic system that favours and rewards the pursuit of economic growth. To navigate these barriers, the cases analysed adopted various innovative approaches, such as fostering alternative funding schemes, ways to acquire farmland and technology. While their bottom-up approaches are important, the inertia of dominant food systems impedes transitions to alternatives. We suggest that exnovation – the process of deliberately phasing out unsustainable practices – warrants more attention. For example, exnovating goals, policies, and performance metrics that prioritise economic growth at the expense of sustainability could play a crucial role in unlocking post-growth models. This study provides an orientation for further theoretical and empirical research about post-growth food systems transitions and stresses the value of engaging more with the wider political, economic, and legal foundations of transitions.
Keywords: Social enterprise; Not-for-profit business; post-growth economy; Post-growth food